2021
DOI: 10.1097/bpo.0000000000001867
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Graft Extraction From the Femoral Condyle for Fresh Osteochondral Allograft Transplantation in Treating Osteochondritis Dissecans of the Capitellum: Best Fit Based on Radius of Curvature

Abstract: Background: Osteochondritis dissecans (OCD) of the capitellum is a common cause of pain and dysfunction in adolescents that engage in repetitive elbow loading. For large, unstable lesions fresh osteochondral allograft transplantation (FOCAT) from the femoral condyle has been described as an effective treatment. Current practice involves significant guesswork in obtaining an appropriately sized graft, with anatomic variations resulting in poor graft fit. No studies currently exist that analyze and identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Conservative management including cessation of sports has proved effective in the pediatric population 12,13 . Goldstein et al found the radius of curvature of the LFC is similar to the capitellum 6 . In addition, the larger width of the LFC allows its use in larger lesions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Conservative management including cessation of sports has proved effective in the pediatric population 12,13 . Goldstein et al found the radius of curvature of the LFC is similar to the capitellum 6 . In addition, the larger width of the LFC allows its use in larger lesions.…”
Section: Discussionmentioning
confidence: 95%
“…The femoral condyle has a similar radius of curvature to the capitulum, making it a favorable choice to use in an elbow graft 6 . MFC grafts are in high demand, and their limited availability can result in prolonged waiting times.…”
mentioning
confidence: 99%
“…Many studies have evaluated donor sites with similar cartilage thicknesses and contours for other joints because there is a difference in biology and composition according to cartilage thickness. [23][24][25][26][27] Although there are few studies on the appropriate donor for the MCP head, the metatarsal head [28] and a nonarticular part of the affected MCP [29] were used as donors in OCD of the MCP head. However, revision surgery, such as removal of the fixation device, was needed, and a decreased range of motion was reported.…”
Section: Discussionmentioning
confidence: 99%